Pemberdayaan Masyarakat Menuju Desa Sehat dan Bersinar (Bersih Narkoba) di Desa Tea Malala Kecamatan Ulaweng Kabupaten Bone - zaenab, Zaenab; Khaer, Ain; Sudarianto, Sudarianto (STIKES Yayasan RS.Dr.Soetomo, 2025)
Tea Malala Village faces suboptimal sanitation issues and an increasing threat of drug abuse. The lack of clean water facilities and insufficient education about the dangers of drug abuse are major challenges that need to be addressed. The objective of this community service program is to reduce the risk of disease transmission caused by poor sanitation through education on proper waste management and sanitation, as well as to raise awareness about the dangers of drug abuse and establish anti-drug activist agents within the community. The program was implemented in three stages: preparation, execution, and evaluation. Activities included education on organic and inorganic waste management, drug abuse prevention counseling, and the establishment of anti-drug activist agents in the village. Before the program, only 12% of the community practiced waste segregation, but this number increased after the educational sessions. Additionally, the ownership of waste bins increased to 70%, and all households now have proper latrines. In terms of drug prevention, 100% of participants joined the establishment of the